Influence of genetic polymorphisms and habitual caffeine intake on the changes in blood pressure, pulse rate, and calculation speed after caffeine intake: A prospective, double blind, randomized trial in healthy volunteers - Tatsuya Yoshihara; Masayoshi Zaitsu; Fumie Shiraishi; Hisatomi Arima; Fumi Takahashi-Yanaga; Masaki Arioka; Shunichi Kajioka; Toshiyuki Sasaguri (Elsevier, 2019)
The aim of this study was to investigate the contribution of gene polymorphisms, in combination with habitual caffeine consumption, to the effect of caffeine intake on hemodynamic and psychoactive parameters. A double-blind, prospective study was conducted with 201 healthy volunteers randomly allocated 2:1 to the caffeinated group (150 mL decaffeinated coffee with additional 200 mg caffeine) or decaffeinated group (150 mL decaffeinated coffee). We measured the changes in blood pressure (BP) and calculation speed upon coffee intake, stratifying with gene polymorphisms, e.g., those in adenosine A2A receptor (ADORA2A) and cytochrome P450 (CYP) 1A2, and daily caffeine consumption (≤90 mg/day and >90 mg/day). Overall, caffeine intake independently increased BP and calculation speed (p-values < 0.05), irrespective of the polymorphisms. In stratified analysis, a statistical significance within the caffeinated group was observed for the change in systolic BP in the stratum of CYP1A2 polymorphism with daily caffeine consumption ≤90 mg/day: change in systolic BP in the CYP1A2 rs762551 CC group (mean ± SD = 11.8 ± 5.9) was higher than that in the AA/CA group (4.1 ± 5.5). Gene polymorphisms may limitedly modify the effect of caffeine intake on hemodynamic parameters in combination with habitual caffeine consumption. Keywords: Caffeine, ADORA2A, CYP1A2, Polymorphism, Blood pressure